Analisis Manajemen Investasi Publik dalam Perspektif Etika Bisnis Islam: Studi Terhadap Efektivitas dan Kepatuhan Syariah - Mursidah, Mursidah (CV. Lentera Literasi Indonesia, 2025)
This study aims to analyze the management of public investment from the perspective of Islamic business ethics, with a focus on the effectiveness of management and the level of compliance with sharia principles. The method used is library research with a qualitative descriptive approach. Data were obtained through a review of academic literature, statutory regulations, fatwas issued by the National Sharia Council (DSN-MUI), and official reports from public investment management institutions such as BPKH and the Directorate General of Budget Financing and Risk Management (DJPPR) of the Ministry of Finance. The analysis employed content analysis focusing on Islamic ethical values such as trust (amanah), justice (adl), and public benefit (maslahah), as well as principles of sharia compliance such as the prohibition of usury (riba), uncertainty (gharar), and gambling (maysir). The results show that normatively, Indonesia’s public investment management system has established a legal and institutional framework that supports sharia principles. However, its implementation still faces several challenges, particularly in terms of outcome effectiveness and adherence to Islamic ethical standards. This study recommends strengthening sharia governance in public investment policy to ensure the achievement of social justice and sustainable Islamic-based economic development.